2013
DOI: 10.1073/pnas.1220417110
|View full text |Cite
|
Sign up to set email alerts
|

Protein cold adaptation strategy via a unique seven-amino acid domain in the icefish ( Chionodraco hamatus ) PEPT1 transporter

Abstract: Adaptation of organisms to extreme environments requires proteins to work at thermodynamically unfavorable conditions. To adapt to subzero temperatures, proteins increase the flexibility of parts of, or even the whole, 3D structure to compensate for the lower thermal kinetic energy available at low temperatures. This may be achieved through single-site amino acid substitutions in regions of the protein that undergo large movements during the catalytic cycle, such as in enzymes or transporter proteins. Other st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…In plants, these transporters are key players in nitrogen nutrition and therefore plantlet growth. The importance of oligopeptide transport to tolerate cold is corroborated by the demonstrated molecular adaptation of this transporter family in antarctic icefish ( Chionodraco hamatus ) adapted to sub‐zero temperatures (Maffia et al ; Rizzello et al ). The role in N nutrition of these transporters in animal and plants indicates that nutrient transport can be a limiting factor at low temperature that likely limits remobilization of seed stocks and/or absorption and transport of N from roots to aerial organs.…”
Section: Discussionmentioning
confidence: 95%
“…In plants, these transporters are key players in nitrogen nutrition and therefore plantlet growth. The importance of oligopeptide transport to tolerate cold is corroborated by the demonstrated molecular adaptation of this transporter family in antarctic icefish ( Chionodraco hamatus ) adapted to sub‐zero temperatures (Maffia et al ; Rizzello et al ). The role in N nutrition of these transporters in animal and plants indicates that nutrient transport can be a limiting factor at low temperature that likely limits remobilization of seed stocks and/or absorption and transport of N from roots to aerial organs.…”
Section: Discussionmentioning
confidence: 95%
“…rabbit) and not to the zebrafish model. Interestingly, when functionally analysed, the Atlantic salmon PEPT1 exhibited only a slight pH dependence of the maximal transport rate (Rønnestad et al ) while the Antarctic icefish showed no pH dependence of the maximal transport rate (Rizzello et al ), which suggests conformance of both transporters to the rabbit/sea bass paradigm.…”
Section: The Teleost Fish Model: General Featuresmentioning
confidence: 99%
“…However, in the Antarctic icefish (polar poikilotherm living at −1.9°C; http://www.fishbase.org) it has recently been found that a de novo domain composed of one to six repeats of seven amino acids (VDMSRSK), placed as an extra stretch in the cytosolic COOH‐terminal region of PEPT1 (Supplemental Fig. S1), contributes in part – but per se – to cold adaptation (Rizzello et al ). VDMSRSK is in a protein region not involved in transport activity and, notably, when transferred to the COOH terminus of the rabbit (warm‐adapted) transporter, it confers cold adaptation to this protein.…”
Section: The Teleost Fish Model: General Featuresmentioning
confidence: 99%
“…Interestingly, there was no significant change in L ‐ala‐ala uptake rate with altered mucosal pH (Figure ). This is distinct from studies in the nematode Caenorhabditis elegans , teleosts and mammals, which describe pH‐dependence of dipeptide uptake and an optimum uptake occurring from pH 5.5–6.0 (Benner et al ., ; Fujisawa et al ., ; Rizzello et al ., ; Spanier, ). Conversely, zebrafish Danio rerio (Hamilton 1822) have an elevated rate of transport at more alkaline pH (8.5).…”
Section: Discussionmentioning
confidence: 99%